Legal Analysis of the Importance of Legal Protection for Victims of Identity Forgery Crimes - Eko Sahputra; Henry Aspan (PT. Sinergi Legal Publisher, 2026)
Indonesia is a country of law, with various legal regulations in place to protect a person's rights. However, this does not make Indonesia free from crime. Theft often occurs in society, with various methods, one of which is through identity fraud. Identity is a characteristic, sign, or identity inherent in a person, evidenced by an authentic deed. Having an identity is crucial in national life, as without it, it will be difficult to obtain legal protection and certainty in any relationship that arises or disappears in the interests of national life. The protection for owners of falsified personal data on the Pre-Employment Card assistance website is stipulated in Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions and Law Number 27 of 2022 concerning Personal Data Protection. This study uses a normative legal research method. Data collection was conducted through literature and document studies. Data analysis was conducted using descriptive analytical methods and a qualitative approach. The results of the study indicate that the implementation of personal data protection efforts is still far from being implemented, thus posing a risk of personal data leaks, which can lead to other related crimes such as identity forgery, identity misuse, and illegal identity trading, which result in losses for personal data owners.